An isolated DC-DC converter with +/-220V balanced outputs for telecom systems - Seixas, F. J.M. [UNESP]; Bascopé, G. V.T. [UNESP]; Barbi, I. [UNESP] (My University, 2001)
This work proposes a new strategy to improve the double-output DC-to-DC converter. The isolated full-bridge topology is zero-voltage switched (ZVS) and the pulse-width modulation is phase-shifted (PS-PWM). The high-frequency isolation transformer has two secondary windings to feed both the +220V and -220V DC outputs. The output filtering inductors are coupled together to balance the output voltages. A very simple command circuit, using only one integrated circuit, is employed to obtain regulated DC outputs and to drive the switches.